Advocacy counterstrategies to tobacco industry interference in policymaking: a scoping review of peer-reviewed literature - Britta K. Matthes; Praveen Kumar; Sarah Dance; Tom Hird; Angela Carriedo Lutzenkirchen; Anna B. Gilmore (BMC, 2023)
Abstract Background There has been remarkable tobacco control progress in many places around the globe. Tobacco industry interference (TII) has been identified as the most significant barrier to further implementation of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC). Civil society has been recognised as a key actor in countering TII. While TII has been extensively studied for several decades now, there is little research that focuses on counteractions to limit it and their effectiveness to do so. This scoping review seeks to map the peer-reviewed literature on civil society's activities of countering TII in policymaking to identify common counterstrategies and assess their effectiveness. Methods Data sources: We searched Embase, IBSS, JSTOR, PubMed, Science Direct, Scopus and Web of Science using the following terms: ("Tobacco industry" OR "Tobacco compan*") AND. ("corporate political activity" OR "CPA" OR "lobbying" OR "interference") AND ("advoca*" OR "counter*" OR "activi*"), without time or language restrictions. Study selection: Our selection criteria included peer-reviewed studies that were written in English, German, or Spanish that drew on primary data and/or legal and policy documents and reported at least one specific example of civil society members or organisations countering tobacco industry action-based strategies. Data extraction: Advocates' counterstrategies were analysed inductively and countered industry strategies were analysed using the Policy Dystopia Model (PDM). Perceptions of effectiveness of countering attempts were analysed descriptively. Results We found five common counterstrategies among 30 included papers covering five WHO regions; 1. Exposing industry conduct and false claims; 2. Accessing decision-makers; 3. Generating and using evidence; 4. Filing a complaint or taking legal action; 5. Mobilising coalition and potential supporters. These counterstrategies were used to work against a wide range of industry strategies, which are captured by five action-based strategies described in the PDM (Coalition Management, Information Management, Direct Access and Influence, Litigation, Reputation Management). While some studies reported the outcome of the countering activities, their impact remained largely underexplored. Conclusion The review shows that peer-reviewed literature documenting how civil society actors counter TII is scarce. It suggests that advocates employ a range of strategies to counter TII in its different forms and use them flexibly. More work is needed to better understand the effects of their actions. This could stimulate discussions about, and facilitate learning from, past experiences and help to further enhance advocates' capacity.